Assessing the pollutant removal potential of native reeds in sewage and paper mill effluents - Monica, K B; Maheswari, M; Dhevagi, P; Kokiladevi, E; Chitdeshwari, T; Sivakumar, U (Plant Science Today, 2025)
Reed plants are cost effective method of remediating the wastewater. To test the removal efficiency of pollutants from sewage and paper mill effluents, four different reed plant species, Canna indica (Indian Shot), Colocassia esculenta (Taro), Typha domingensis (Southern Cattail) and Xanthosoma sagittifolium (Tannia), were compared for their removal efficiency of pollutants from sewage and paper mill effluents. Because of the high cost and limited effects of present physico-chemical treatments in wastewater treatment plant, this reed bed system can act as a cheaper process, that are essential to remove the organic pollutants, thus make them suitable for agricultural and irrigation purposes. In this study, initially, the raw effluent of sewage and paper mill was characterized. The four reed plants were separately screened with both the effluents by adopting the treatments for the four reeds and seven days retention time as two factors with 2 replications in pots. Each day, the treated effluent was collected from the pot and analysed. Up to day 7, the screening was done with both the effluents. The result shows that the Canna indica and Colocassia esculenta could be the better option for pollutant removal from the sewage and paper mill effluent respectively. The removal efficiency was higher in Canna indica (60%) for sewage wastewater and Colocassia esculenta (65%) for paper mill effluent. This removal percentage shows that the tolerating nature of the plants to the wastewater. The efficiency of the removal of pollutant by reeds can be further improved by bioaugmentation process which aids the action of microbes in the rhizosphere of the reed plants which may be used in the reed bed system.